Біологічні особливості і нагромадження ефірної олії Salvia sclarea L. в умовах Херсонської області - Svidenko, S.V.; Lichinkina, N.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The biological peculiarities and accumulation of essential oil by Salvia sclarea L. in the conditions of the south of Ukraine's steppe zone (Kherson region) were investigated. It was revealed that the most quantity of oil (on average 0,20%) accumulate in the end of flowering – the beginning of fruit-bearing phase, linalilazetat prevails in oil. It is recommended to grow this plant in the Kherson region.